SERVICE FOR FOREIGN TOUR GROUPS IN MOSCOW AS A COMPONENT OF THE TOURIST REGION IMAGE (BASED ON 2015-2016) - N. Zamyatina; A. Zbarskaya (Вестник университета)
The article covers issues of the notion and formation of a tourist region image and considers problems of the service for inbound tourists in Moscow Region.